Faster referral and surgical intervention for rhegmatogenous retinal detachment during COVID-19: a comparison of pre- and during-pandemic cases - Ali Momeni; Hassan Asadigandomani; Mahdi Jamalitootakani; Mohammadreza Mehrabi Bahar; Hooshang Faghihi; Fariba Ghassemi; Elias Khalili Pour; Hamid Riazi-Esfahani (Scientific Reports)
Abstract To investigate the impact of the COVID-19 pandemic on the incidence and clinical characteristics of rhegmatogenous retinal detachment (RRD) patients referred to a high-volume center, Farabi Eye Hospital, Iran. In a retrospective study, all new RRD patients referred to Farabi Eye Hospital between March 2019 and March 2020 (pre-pandemic, Group 1) and March 2020 and March 2021 (post-pandemic, Group 2) were analyzed. The groups were compared based on demographic and clinical data. A total of 375 patients were included (131 pre-pandemic, 244 post-pandemic, and 34 during lockdowns). The during-pandemic group had a shorter referral time (44.97 vs. 76.76 days, p = 0.031) and surgical wait time (4.64 vs. 8.63 days, p < 0.001). No significant differences were found in pre-operative features (etiology, proliferative vitreoretinopathy, break type), surgical procedures, or initial treatment failure rates between the groups. General anesthesia use was significantly higher in the during-pandemic group (81.6% vs. 71.8%, p = 0.029). The COVID-19 pandemic did not significantly alter the demographic, clinical characteristics, or initial surgical outcomes of RRD patients. However, patients were referred and treated more expeditiously during the pandemic. The increased use of general anesthesia requires further investigation.